Pengaruh Kreativitas Dan Inovasi Terhadap Minat Beli Konsumen Bakso O’Boss Di Kota Bengkulu - Gita Carlina; Sri Ekowati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aimed to find out the effect of creativity and innovation on consumer buying interest in Bakso O’Boss in Bengkulu City. The sample of this study was the consumer of Bakso O’Boss, amounting to 130 people. This type of research uses quantitative research by distributing questionnaires for data collection. The results of the study indicate that the variables of creativity and innovation have a positive and significant effect on consumer buying interest.